Agricultural GHGs: from a Global Research Alliance to shared policies and practices - Reisinger, Andy (International conference on agricultural greenhouse gas GHG emissions and food security, 2018)
Opening keynote presentation at the International conference on agricultural greenhouse gas GHG emissions and food security in September 10-13, 2018, Berlin, Germany.